Validity Analysis of VR-Based Particle Dynamics Module Development Using the Rasch Model - Supurwoko Supurwoko; Kadek Dwi Hendratma Gunawan; Muhammad Nur Hudha (Online Learning In Educational Research (OLER), 2025)
Physics education often encounters challenges in fostering students’ conceptual understanding of particle dynamics, largely due to the abstract nature of the content and its reliance on symbolic mathematical representations, which can impede meaningful interpretation of physical phenomena. To address this issue, this study developed PADYVIR (Particle Dynamics Virtual Reality), a virtual reality–assisted learning module, and examined its validity, reliability, and practicality for use in higher education settings. The development process followed the ADDIE instructional design model, after which the module underwent expert appraisal and psychometric evaluation using the Rasch measurement model. Expert assessments involved physics education specialists and instructional design experts, who evaluated the content, construct clarity, and pedagogical appropriateness of PADYVIR and its supporting learning instruments. The research instruments used in this study were adapted from previously validated tools reported in the literature, thereby ensuring the validity of baseline measurements. Rasch analysis indicated strong psychometric properties, including high person and item reliability indices, acceptable fit statistics, and evidence of unidimensionality. A limited trial with undergraduate students further demonstrated the high practicality of the system in terms of usability, attractiveness, and comprehensibility. These findings confirm that PADYVIR is a psychometrically robust and user-friendly instructional resource capable of supporting the visualisation and conceptual learning of particle dynamics. Methodologically, the study contributes to the field by integrating rigorous measurement theory with immersive educational technology, offering a replicable framework for the development and evaluation of virtual reality–based learning media. Implications for instructional design and educational technology research are discussed, and directions for future effectiveness studies are proposed